Role of temperament in early adolescent pure and co-occurring internalizing and externalizing problems using a bifactor model: Moderation by parenting and gender. (9th December 2015) - Wang, Frances L.; Eisenberg, Nancy; Valiente, Carlos; Spinrad, Tracy L.
Abstract: We contribute to the literature on the relations of temperament to externalizing and internalizing problems by considering parental emotional expressivity and child gender as moderators of such relations and examining prediction of pure and co-occurring problem behaviors during early to middle adolescence using bifactor models (which provide unique and continuous factors for pure and co-occurring internalizing and externalizing problems). Parents and teachers reported on children's (4.5- to 8-year-olds; N = 214) and early adolescents' (6 years later; N = 168) effortful control, impulsivity, anger, sadness, and problem behaviors. Parental emotional expressivity was measured observationally and with parents' self-reports. Early-adolescents' pure externalizing and co-occurring problems shared childhood and/or early-adolescent risk factors of low effortful control, high impulsivity, and high anger. Lower childhood and early-adolescent impulsivity and higher early-adolescent sadness predicted early-adolescents' pure internalizing. Childhood positive parental emotional expressivity more consistently related to early-adolescents' lower pure externalizing compared to co-occurring problems and pure internalizing. Lower effortful control predicted changes in externalizing (pure and co-occurring) over 6 years, but only when parental positive expressivity was low. Higher impulsivity predicted co-occurring problems only for boys. Findings highlight the probable complex developmental pathways to adolescent pure and co-occurring externalizing and internalizing problems.